AI*IA 2016 advances in artificial intelligence : XVth International Conference of the Italian Association for Artificial Intelligence, Genova, Italy, November 29 - December 1, 2016, proceedings /: XVth International Conference of the Italian Association for Artificial Intelligence, Genova, Italy, November 29 - December 1, 2016, proceedings. (2016) - Unknown
No abstract available